Secondary mathematics teachers’ beliefs about mathematics assessment and components that influence these beliefs - Barkatsas, Anastasios N.; Malone, John A. (NOMAD Nordic Studies in Mathematics Education, 2005)
The espoused beliefs of 465 secondary mathematics teachers regarding mathematics assessment are the focus of this study. The data for this investigation were collected using a 19 items questionnaire. There is evidence from this study that there are teachers who espouse a ’socio-constructivist’ orientation to mathematics assessment, teachers who espouse a ’problem solving’ orientation to mathematics assessment and teachers who espouse an ’accountability’ orientation to mathematics assessment.